14-7p=-7(p-1)

Simple and best practice solution for 14-7p=-7(p-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14-7p=-7(p-1) equation:


Simplifying
14 + -7p = -7(p + -1)

Reorder the terms:
14 + -7p = -7(-1 + p)
14 + -7p = (-1 * -7 + p * -7)
14 + -7p = (7 + -7p)

Add '7p' to each side of the equation.
14 + -7p + 7p = 7 + -7p + 7p

Combine like terms: -7p + 7p = 0
14 + 0 = 7 + -7p + 7p
14 = 7 + -7p + 7p

Combine like terms: -7p + 7p = 0
14 = 7 + 0
14 = 7

Solving
14 = 7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 14x=3(2x+72) | | (5-3)x(-2)= | | 136=-8(1+6V) | | 14-7p=-7p(p-1) | | 3a-7z=6 | | (12x-8)= | | -6g+30=6 | | .30/(y-1.43)=x | | r+441=-225 | | 11w-13w=12 | | 1+7a=1+4a+2a-5 | | -5y+2=37 | | N+9=3*6 | | 3(w-2)+4=2w+5 | | k/24=25 | | 26q=-832 | | 7x+25=3x+50 | | -7-7x+4x=-25 | | z=1+2i | | 6x+3.8=1x+19 | | -3x^2+12x+1=y | | 11w-13=12 | | 8x+9=3x+1+4x+5 | | m+4=57 | | f(3)=3(3)+2 | | 4(p-3)=-16 | | 2p=56 | | 7=k+1/8 | | 4x-8=7x+10 | | -13-8b=3-3b-7b | | 2a+6z=4 | | X+5+3x=x |

Equations solver categories